European Radiology Experimental - Sardanelli, Francesco
European Radiology Experimental is a fully open access official journal of the European Society of Radiology. Its mission is to adhere to the multidisciplinary paradigm of the 21st century, fostering a strong connection between radiology in the experimental setting and basic science. Research on phantom studies, cell models and radiobiology, animal models, new modalities/techniques (e.g., MR sequences or spectral CT applications, molecular, hybrid, and optical imaging), novel contrast materials, tracers, and probes are welcome. Other topics fully considered are: 3D-modelling, printing, and simulation; advanced teleradiology (e.g., virtual physician-patient interaction); novel image reconstruction algorithms and post-processing. Studies on humans are also suitable for publication, especially if they are proof of concept or explorative studies, concern computer-assisted detection/diagnosis, data extraction for risk stratification or prognosis, or innovative approaches to clinical study design. Manuscripts reporting innovation for interventional radiology, imaging biomarkers, radiogenomics, or new clinical decision support systems are also welcome. The goal of the journal is to provide a forum open not only to radiologists, nuclear physicians, or radiation therapists but also to other professionals such as physicists, biologists, chemists, bioengineers, and biomathematicians, experts in computer science, information technology, and bioinformatics, as well physicians working in medical imaging from other medical specialties such as pathologists, geneticists, neurologists, surgeons, cardiologists, and many more.